KOREKSI TUTURAN OLEH SBY (STUDI KASUS WAWANCARA KHUSUS â€œSAATNYA SBY BICARAâ€ DI METRO TV) - Widyastuti, Susana (English Department FBS UNP, 2010)
This research aims at describing the reasons, mechanism and forms of self-repair as well as describing the relationship betweenÂ the employment of self-repair and SBY as the speaker. Data of the research were SBYâ€™s utterances in an exclusive interview called â€œSaatnya SBY Bicaraâ€ broadcasted by Metro TV. Data were transcribed and analyzed carefully using qualitative method as the main method and quantitative method as the supporting method to provide frequency of data occurance. The research findings show that there are two main reasons of the employment of self-repair by SBY, they are the problems of speaking and understanding. Two mechanism of self-repair found are self-initiated self-repair (SISR) and other-initiated self-repair (OISR). In the mechanism of SISR, SBY employs three forms of repair (R), they are word search, word/phrase replacing, and explanation. These three forms of repair are preceded by two forms of repair-initiation (RI), they are lexical markers and non-lexical markers. In the mechanism of OISR, SBY employs four forms of repair (R), they are accepting, rejecting, explaining and limiting statement. These four forms of repair are preceded by three forms of repair-initiation (RI), they are clarification, non-understanding, and interpretation. The employment of self-repair reflects SBY as the speaker, such as SBY as a competent and careful person, and SBY asÂ a polite person who tries to maintain good relationship with others and not to hurt othersâ€™ feeling.Â